Construction of recombinant newcastle disease virus expressing granulocyte-macrophage colony-stimulating factor - Fikri Ooi, Nur Zafirah (2022)
Cancer continues to surpass human intervention for decades. The cancer mortality rate increases every year and there is neither a single treatment that is suitable for all tumours at different stages nor it could eliminate tumour completely. Clearly, alternative treatments to accommodate the demanding disease are anticipated. One of such treatments is oncovirotherapy – the use of virus as a therapeutic agent for cancer. Newcastle disease virus (NDV) is a promising anti-cancer agent because it selectively infects and replicates in cancer cells without harming the normal cells. To further enhance the oncolytic activity, NDV can be manipulated via reverse genetics to harbour and express immunomodulatory gene in NDV-infected cancer cells. The aim of this study was to construct two recombinant NDVs (rNDV) that express human and murine granulocyte-macrophage colony-stimulating factor (hGM-CSF and mGM-CSF). These genes were amplified from lipopolysaccharide (LPS)-induced human myeloid leukaemia cells and murine colorectal carcinoma cells, respectively, and were cloned into NDV antigenome plasmid, pOLTV5 (rAF-GFP). The plasmids were co-transfected with helper plasmids (pCIneoNP, pCIneoP, and pCIneoL) into BSR T7/R5 cells to produce the recombinant NDVs, designated as rAF-GFP/hGM-CSF and rAF-GFP/mGM-CSF. Genomes of the viruses were extracted and verified by DNA sequencing followed by a large-scale propagation of the virus using 9-day old embryonated egg. The expression of both GM-CSF genes was determined via ELISA. High hGM-CSF and mGM-CSF glycoproteins were expressed by both rAF-GFP/hGM-CSF and rAF-GFP/mGM-CSF virus during viral infection in human colorectal carcinoma cells. In migration assay, human myeloid leukaemia cells and mouse macrophage cells that were seeded on top of collagen matrix gel were shown to be attracted towards the human colorectal carcinoma infection supernatant containing hGM-CSF and mGM-CSF in 24 hours and 12 hours, respectively. In conclusion, rAF-GFP/hGM-CSF and rAF-GFP/mGM-CSF virus produced in this study successfully express hGM-CSF and mGM-CSF genes upon infection and they are biologically active as verified through migration assay. This warrant a further investigation for their potential to be used for cancer treatment.